The insights from X-ray absorption spectroscopy into the local atomic structure and chemical bonding of Metal–organic frameworks. (15th November 2018) - Soldatov, Mikhail A.; Martini, Andrea; Bugaev, Aram L.; Pankin, Ilia; Medvedev, Pavel V.; Guda, Alexander A.; Aboraia, Abdelaziz M.; Podkovyrina, Yulia S.; Budnyk, Andriy P.; Soldatov, Alexander A.; Lamberti, Carlo
Graphical abstract: The review is devoted to the X-ray absorption spectroscopies (XAS) which are among the most powerful techniques for characterization of local atomic and electronic structure of metal atmos in MOFs. XAS is element selective technique, sensitive to local atomic coordination, bond lengths and angles, oxidation state of metals atoms. Abstract: After a short introduction highlighting the potentialities of metal–organic frameworks (MOFs) and the power of X-ray absorption spectroscopies (XAS), a list of selected examples follows. The first part of this review provides the basic concepts that are behind the most used XAS techniques: Extended X-ray Absorption Fine Structure (EXAFS) and X-ray Absorption Near Edge Structure (XANES) spectroscopies. Moreover, it reports also the basis of an innovative approach to the EXAFS data analysis based on the wavelet transform approach, that allows a more solid attribution to the different paths contributing to the overall signal. The second part is devoted to provide a section of examples where EXAFS and XANES techniques have been determinant in understanding the structural and electronic properties of metal centers in MOFs. The selected examples have been ordered in subsections related to the application foreseen for the investigated MOFs materials: MOFs functionalization for catalytic applications; MOFs as single site catalyst; MOFs as photocatalysts; MOFs for gas sorption and storage; MOFs for energy application. Conclusions and perspectives are provided at the end.